PENGELOLAAN MEDIA SOSIAL SEBAGAI MEDIA PROMOSI PASAR DIGITAL CIKUNDUL SUKABUMI - Mulyana, Slamet; Octavianti, Meria; Faradysa, Nadila Zahara (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2019)
Cikundul is a digital market and a new tourism destination actively operating in Sukabumi, West Java. The promotion of the digital market is conducted by optimizing social media, which is managed by Generasi Pesona Indonesia (GenPI; lit. the Generation of Enchanting Indonesia) Sukabumi. This study aims to describe the management of social media as tourism promotion media for Cikundul Market, from planning to implementation to evaluation. Case study was the approach employed to provide a comprehensive view of object under study. The subject of the study was multi sources, with key informants comprising bureaucrats, academics, community leaders and the market visitors. Data was collected through interviews, observations, and literary studies.The results showed that Cikundul Market applied two concepts of digital market, i.e. the beauty of nature and the attractiveness of infrastructure, in order to improve the tourism destination and to attract tourists. The management of social media as promotion media was conducted in several stages: content research, content processing, content upload to official media, and evaluation of social media impressions. Promotion management was carried out by GenPI Sukabumi by optimizing the existing resources in realistic manner.